Non-market considerations: the socio-political imperative in international business - Devinney, Timothy (Henry Stewart Talks, 2014)
Socio-political imperative, Political risk, Political instability, Economic freedom, Corruption, State capture, Civil liberties, freedom and development, The dividends of good governance, Political risk, country risk and project risk, Interest groups, Stakeholders, Political risk, Corporate reactions to stakeholders, Global stakeholders v stakeholders globally, The role of global monitors
Updated at 2014/04/06, Reviewed at 2024/05/03